Experimental and numerical analysis of the static strength and fatigue life reliability of parabolic leaf springs in heavy commercial trucks - Ceyhanli, Ufuk Taner; Bozca, Mehmet (SAGE PUBLICATIONS LTD, 2020)
The objective of this study is to perform experimental and numerical analysis of the static strength and fatigue life reliability of parabolic leaf springs in heavy commercial trucks. To achieve this objective, stress and displacements under static loading were analytically calculated. A computer-aided design model of a parabolic leaf spring was created. The stress and displacements were calculated by the finite element method. The spring was modelled and analysed using CATIA Part Design and ANSYS Workbench. The stress and displacement distributions on a three-layer parabolic leaf spring were obtained. The high-strength 51CrV4 spring steel was used as sample parabolic leaf springs material, and heat treatments and shoot peening were applied to increase the material strength. Sample parabolic leaf springs were tested to obtain stress and displacement under static loading conditions. By comparing three methods, namely, the static analytical method, static finite elements method and static experimental method, it is observed that results of three methods are close to each other and all three methods are reliable for the design stage of the leaf spring. Similarly, sample parabolic leaf springs were tested to evaluate the fatigue life under working conditions. The reliability analysis of the obtained fatigue life test value was carried out. It was shown that both analytical model and finite element analysis are reliable methods for the evaluation of static strength and fatigue life behaviour in parabolic leaf springs. In addition, it is determined by a reliability analysis based on rig test results of nine springs that the spring achieves its life cycle of 100,000 cycles with a 99% probability rate without breaking. Furthermore, the calculated fatigue life is 2.98% greater than experimentally obtained fatigue life mean and the leaf spring can be used safely and reliably during the service period in heavy trucks.
Keywords: Parabolic leaf spring; fatigue behaviour; finite elements; reliability; microstructure; Thermodynamics; Engineering